Pengembangan Materi Sejarah Kebudayaan Islam sebagai Bahan Ajar Literasi Membaca di Madrasah Ibtidaiyah - Alfin, Jauharoti (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2019)
This research focus upon the development of learning materials in History of Islamic Civilization (SKI) Subject for reading literacy in Bahasa Indonesia subject. The research emphasizes upon the implementation of learning strategy. As the foundation, the research process follows guidelines of School Literacy Program (GLS) and Program for International Student Assessment (PISA) standard of achievement. By the two standards, the researcher does not only follow school literacy development framework but also measuring students’ achievement under internationally recognized standards. Within research and development framework of Borg and Gall, researcher selected an Islamic school that has attempted to integrate literacy program into other subjects but was yet unsuccessfully improve their students’ literacy level. As the end product of this research, learning materials and instructions have been designed in a way of reading literacy program as well as deepening students’ comprehension towards related school subject.